Juridical Study of Regulation of the Minister of Education, Culture, Research, and Technology Number 46 of 2023 concerning the Prevention and Handling of Violence in the Environment of Education Units - Ade Ria Julista; Lukman Hakim; Edi Saputra Hasibuan (Greenation International Journal of Law and Social Sciences, 2024)
Human rights are rights that God has given to humans since birth. Lawsuits in Indonesia cannot interfere with human rights because this country is very protective of human rights. The right to a decent education is one of many human rights. The protection of human rights, especially in the field of education, is necessary so that human rights in Indonesia can be properly implemented. The purpose of protecting human rights in the field of education is to prevent human rights violations in the field of education, such as the emergence of bullying incidents in schools, which have negative consequences, one of which is the emergence of violence, both verbally and physically. In Indonesia, there are still many cases of child abuse. Even with the rapid flow of information, cases of bullying also often occur online. This study looks at the Regulation of the Minister of Education, Culture, Research, and Technology Number 46 of 2023 in the function of the Violence Prevention and Handling Team. The normative juridical method is used in this study, which includes various relevant legal rules. The study found that bullying cases are sometimes overlooked by schools.